Breves esclarecimentos sobre o cordel brasileiro:: forma, conteúdo e origem (Revista Internacional de Folkcomunicação, 2024)
Brazilian cordel is a literary genre widely accepted and spread in Brazil, as well as internationally. It is one of the most authentic artistic manifestations we have and despite the fact it was initially consolidated among the inhabitants of the region known nowadays as Northeast, it occupies a special place in schools and libraries. Its material support has overcome its presentation in low cost brochures and now not only it is printed in hardcover books, it also has reached the cyberspace and message apps. Moreover, in spite of the mentioned success, its fundamental characteristics are still unkown for the public in general, as well as the aspects related to its origins. So, this brief study, based on the onthological and historical marxism and its aesthetic, aims at guiding readers to understand what the brazilian cordel really is, at the same time it reinfforces the efforts of those who conclude that this so-called popular poetry mustn’t be seen as a folkloric phenomenon but as part of the national literary canon.